Regulatory scientific advice in drug development: does company size make a difference? - Putzeist, Michelle (Springer-Verlag, 2010)
PURPOSE: To assess whether the content of Scientific Advice (SA) questions addressed to a national drug regulatory agency is associated with company size. This may help to increase understanding about the knowledge, strategic, and regulatory gaps companies face during drug development. METHODOLOGY: A cross-sectional analysis was performed of SA provided by the Dutch Medicines Evaluation Board (MEB) in 2006–2008. Definition of company size was based on ranking by total revenues (Scrip’s Pharmaceutical Company League Tables 2008). The content of each SA question was scored according to predefined domains (quality, nonclinical, clinical, regulatory, and product information), their subdomains (e.g., efficacy), and a selection of additional content variables (e.g., endpoints, choice of active comparator). RESULTS: In total, 201 SA documents including 1,087 questions could be identified. Small, medium-sized, and large companies asked for SA 110 (54.7%), 40 (19.9%), and 51 (25.4%) times, respectively. Clinical questions were asked most often (65.9%), mainly including efficacy (33.2%) and safety questions (24.0%). The most frequent topics were overall efficacy and safety strategy. Small companies asked quality and nonclinical questions more often (P < 0.001) and clinical questions less frequently than large companies (P = 0.004). Small companies asked significantly more clinical questions about pharmacokinetics, including bioequivalence, than medium-sized and large companies (P < 0.001). CONCLUSION: The array of topics addressed in SA provides an interesting outlook on what industry considers to be still unresolved in drug development and worthwhile to discuss with regulators. Company size is associated with the content of SA questions. MEB advice accommodates both innovative and noninnovative drug development.